Effect of Charitable Giving : Donors’ Choice of Governance - Chokkalingam, Tamilchelvi (Advances in Social Sciences Research Journal, 2017)
This study examines how the governance of the Non-Profit Organizations and Charities (NPOs) affect the charitable giving of donors using the regression model and comparing it with the structural equation model. Samples are collected in Singapore and donors’ views are examined. To test the donors’ choice of governance, compliance to governance is taken to be the dependent variable against four independent variable of corporate governance that is roles and responsibilities, information disclosure, accountability and board’s processes. Donors largely agreed that these components are fundamental to good governance and are main contributors to their donations and trust; they would place with the charities and NPOs. Social responsibility and accountability seemed to have a negative influence on the compliance to governance as donors believe that compliance to such governance process will no longer be important if NPOs and charities are proven to be socially responsible and accountable.